CBX2 identified as driver of anoikis escape and dissemination in high grade serous ovarian cancer. (November 2018) - Wheeler, Lindsay; Watson, Zachary; Qamar, Lubna; Yamamoto, Tomomi; Post, Miriam; Berning, Amber; Spillman, Monique; Behbakht, Kian; Bitler, Benjamin
Abstract High grade serous ovarian carcinoma (HGSOC) is often diagnosed at an advanced stage. Chromobox 2 (CBX2), a polycomb repressor complex subunit, plays an oncogenic role in other cancers, but little is known about its role in HGSOC. We hypothesize that CBX2 upregulation promotes HGSOC via induction of a stem-like transcriptional profile and inhibition of anoikis. Examination of Gene Expression Omnibus (GEO) datasets and The Cancer Genome Atlas (TCGA) established that increasedCBX2 expression conveyed chemoresistance and worse disease-free and overall survival. In primary HGSOC tumors, we observed CBX2 expression was significantly elevated compared to benign counterparts. In HGSOC cell lines, forced suspension promoted CBX2 expression. Subsequently, CBX2 knockdown inhibited anchorage-independent proliferation and potentiated anoikis-dependent apoptosis. Furthermore, CBX2 knockdown re-sensitized cells to platinum-based chemotherapy. Forced suspension promoted increased ALDH activity andALDH3A1 expression and CBX2 knockdown led to a decrease in both ALDH activity andALDH3A1 expression. Investigation of CBX2 expression on a HGSOC tissue microarray revealed CBX2 expression was apparent in both primary and metastatic tissues. CBX2 is an important regulator of stem-ness, anoikis escape, HGSOC dissemination, and chemoresistance and potentially serves as a novel therapeutic target.